Southeast Asia's geopolitical centrality and the U.S.-Japan alliance - Bower, Ernest Z.; Hiebert, Murray; Nguyen, Phuong (Research Associate with the Sumitro Chair for Southeast Studies at CSIS); Poling, Gregory B. (a CSIS report, 2015)
Building on a careful analysis of Southeast Asia's recent history, politics, economics, and place within the Asia Pacific, this report looks forward two decades to anticipate the development of trends in the region and how they will impact the U.S.-Japan alliance